Study process of private and public universities students using the revised two factors study process questionnaire (R-SPQ-2F) - Shahfuddin, Wasidah; A. Rahim, Abdul Razak; Abdullah, Mohammad Ridhuan (Vietnam Ministry of Education and Training, 2022)
This research examined the impact of students’ demographic background on the study process of public and private university students. The Revised Two Factor Study Process Questionnaire (R-SPQ-2F) consisting of 20 items was used to collect data from 217 conveniently selected participants from public and private universities. To answer the research questions, descriptive statistics, an independent sample t-test, and a one-way analysis of variance (ANOVA) were employed.The research findings indicate that regardless of university types, students tend to use the deep approach (M=2.685) of learning more compared to the surface approach (M=1.928). The researchers have found statistically significant differences between study approach and gender, types of universities, fields of study, academic level, year(s) of study and ethnicity. The research results reveal that demographic background has a significant influence on students’ approaches to learning. In terms of university type, the results indicated that students at public universities preferred the deep method of learning more (M=2.809, SD=0.515) than students at private universities (M=2.537, SD=0.581).